Leakage protection for carbon-intensive materials post-2020 - Karsten Neuhoff; William Acworth; Roland Ismer; Oliver Sartor; Lars Zetterberg (DIW Economic Bulletin, 2015)
Climate protection is a global challenge that all countries have a common but differentiated responsibility to address. However, not all governments are willing to commit to targets of equal stringency, and individual countries may put different emphases on carbon pricing in their policy mix. Carbon prices may thus continue to differ over longer time horizons. Therefore, measures to protect production of carbon-intensive materials from carbon leakage might be required not only as short-term transition instruments, but also for longer periods. Leakage protection measures therefore need to preserve carbon price incentives for emission mitigation across the value chain. If ex-ante or dynamic free allocation of emission allowances is used as a leakage protection measure, only the primary producers face the full carbon price signal for efficiency improvements. Accordingly, shifts to lower-carbon fuels and the carbon price signal for intermediate and final consumers are muted. Thus a large share of mitigation opportunities cannot be realized. Combining dynamic allocation of allowances with a consumption charge (Inclusion of Consumption into the The European Union Emissions Trading System, EU ETS) or combining full auctioning with Border Carbon Adjustment could reinstate the carbon price signal along the value chain and create incentives for breakthrough technologies, the use of higher-value products with lower weight and carbon intensity, alternative lower-carbon materials and more tailored use of materials. Border Carbon Adjustment is, however, politically contentious as it has often been discussed as an instrument to discriminate against foreign producers. Hence it is important to further explore design details to implement the combination of dynamic allocation with Inclusion of Consumption in the EU ETS.
Keywords: D62; H32; L5; 330; EU ETS; Mitigation; Leakage protection; Allocation